PsycEXTRA Dataset 2012
DOI: 10.1037/e572172013-299
|View full text |Cite
|
Sign up to set email alerts
|

Using Variable-Rate Alerting to Counter Boredom in Human Supervisory Control

Abstract: A low task load, long duration experiment was conducted to evaluate the impact of cyclical attention switching strategies on operator performance in supervisory domains. The impetus for such a study stems from the lack of prior work to improve human-system performance in low task load supervisory domains through the use of design interventions. In this study, a design intervention in the form of auditory alerts is introduced and the effects of the alerts are examined. The test bed consists of a video game-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Within an operational environment, systems need to minimize any disruption from the detectors, especially in safety critical environments. Mkrtchyan et al ( 2012 ) described an ATC interface designed to detect and counter lapses of attention using EEG, thanks to the officer sitting and the stable environment. However, it can be extremely difficult to achieve for pilots and drivers.…”
Section: Limits To Current Approachesmentioning
confidence: 99%
“…Within an operational environment, systems need to minimize any disruption from the detectors, especially in safety critical environments. Mkrtchyan et al ( 2012 ) described an ATC interface designed to detect and counter lapses of attention using EEG, thanks to the officer sitting and the stable environment. However, it can be extremely difficult to achieve for pilots and drivers.…”
Section: Limits To Current Approachesmentioning
confidence: 99%
“…In terms of personality traits, extraversion has been associated with boredom proneness (Ahmed, 1990), but high levels of conscientiousness have shown the opposite effect (Mkrtchyan, Macbeth, Solovey, Ryan, & Cummings, 2012). Other personality traits of those people able to more effectively cope with boredom include the ability to spend time alone, high measures of attentional capacity, and low formal diagnostic indices of psychopathology (Hamilton, Haier, & Buchsbaum, 1984).…”
Section: Personal Precursorsmentioning
confidence: 99%
“…Another method to change task engagement is to simply notify or alert the operator periodically so that he or she could refocus attention to the task. One study has shown that such a strategy can be useful for operators prone to boredom and distracted for a considerable amount of time (Mkrtchyan et al, 2012). Others have suggested that using biofeedback (such as using electroencephalogram [EEG] to monitor physiological processes) and displaying this information to an operator in real time can potentially alert an operator to refocus.…”
Section: Attention Management and Coping Strategy Selectionmentioning
confidence: 99%